2008
DOI: 10.1007/s10545-008-0902-1
|View full text |Cite
|
Sign up to set email alerts
|

Arginine supplementation in four patients with X‐linked creatine transporter defect

Abstract: Nine months of L-arginine supplementation did not show effectiveness in the four patients affected with CRTR-D in this protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 22 publications
2
37
0
4
Order By: Relevance
“…In fact, it has been suggested that L-arginine treatment alone might also increase these demands (Jahangir et al 2009), elevating plasma total homocysteine (tHcys)/methionine ratio. In our own experience, during the period of 2007-2008, we treated our CRTR-deficient patients with L-arginine alone (Fons et al 2008), but we did not detect low plasma methionine or decreased serum folate values (data not shown). In this report, our aim was to monitor folate status in five CRTR patients undergoing Gly/Arg therapy after the serendipitous finding of severe hyperhomocysteinemia in one of these cases.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…In fact, it has been suggested that L-arginine treatment alone might also increase these demands (Jahangir et al 2009), elevating plasma total homocysteine (tHcys)/methionine ratio. In our own experience, during the period of 2007-2008, we treated our CRTR-deficient patients with L-arginine alone (Fons et al 2008), but we did not detect low plasma methionine or decreased serum folate values (data not shown). In this report, our aim was to monitor folate status in five CRTR patients undergoing Gly/Arg therapy after the serendipitous finding of severe hyperhomocysteinemia in one of these cases.…”
Section: Introductionmentioning
confidence: 79%
“…Patients were treated with oral glycine (200 mg/kg/day) and L-arginine (400 mg/kg/day), twice a day for 6 months, according to previously reported experiences (Fons et al 2008;Battini et al 2010). No other changes in patient treatment or diet were made during this time.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Guanidinoacetic acid, a direct precursor of creatine, improved work capacity in women with chronic fatigue syndrome yet markers of tissue bioenergetics were not improved by the intervention (Ostojic et al 2016), suggesting non-energy related role of this compound. Oral L-arginine, another precursor of creatine, positively affected energy metabolism in MELAS syndrome, an inherited disorder of mitochondrial energy metabolism (Rodan et al 2015), while its effectiveness to improve brain bioenergetics in patients with X-linked creatine transporter defect was absent (Fons et al 2008) or minimal (Chilosi et al 2012). Improved muscle bioenergetics and mitochondrial function have been reported recently in children suffering from Duchenne muscular dystrophy treated with L-arginine and metformin for 16 weeks (Hafner et al 2016).…”
Section: Tackling Impaired Bioenergeticsmentioning
confidence: 98%